Integrating discovery learning with ward wall games to enhance elementary students' engagement in energy transformation topics - Yuyun Sukawati; Khairul Rizal; Meriza Faradilla (Pelita International Publishing, 2024)
This study aims to enhance the learning engagement of fourth-grade students at SD Negeri Lamklat, Aceh Besar, on energy transformation by applying the Discovery Learning model integrated with Ward Wall games. The Classroom Action Research (CAR) was conducted over two cycles, each comprising the stages of planning, implementation, observation, and reflection. The research involved 25 fourth-grade students as subjects. Data were collected through observation sheets on learning engagement, learning outcome tests, and field notes. The findings revealed that integrating Discovery Learning with Ward Wall games effectively increased students' engagement. In the first cycle, the average engagement level was 67%, which improved to 84% in the second cycle. Additionally, students’ learning outcomes demonstrated significant improvement. Thus, integrated with Ward Wall games, the Discovery Learning model proved an effective strategy for enhancing student engagement and learning outcomes in energy transformation topics.